PlGF, sFlt-1 and sFlt-1/PlGF ratio: Promising markers for predicting pre-eclampsia - Ola H El-Demerdash; Mona M Zaki; Mohamed O El Maraghy; Doaa M A Elzoghby; Marwa A Abdel-Wahed; Ahmed M Mamdouh (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2018)
Objective: To evaluate placental growth factor (PlGF) and soluble fms-like tyrosine kinase-1 (sFlt-1) as early predictors of pre-eclampsia.  Methods: Cohort study at Department of Obstetrics and Gynecology, Ain Shams University Hospitals, enrolling eighty pregnant women between 14 and 19 weeks' gestation, sera were collected, and stored at -80°C. Thirty women developed pre-eclampsia, fifty continued to be normotensive and their second blood samples were collected. Serum sFlt-1 and PlGF were assayed using chemiluminescence. All enrolled subjects were divided into Q1, Q2, Q3 and Q4 according to serum levels of sFlt-1, PlGF and sFlt-1/PlGF.  Results: The combined sFlt-1/PlGF ratio (cut-off 40) and PlGF (cut-off 328 pg/mL) had high overall diagnostic performance for early prediction of pre-eclampsia during the second trimester. The Odds ratio for the occurrence of pre-eclampsia was 5.4 in Q4 versus Q3 women and 4.05 higher in Q3 versus Q2 women. Women in Q2 and Q1 had similar risk for developing pre-eclampsia.  Conclusion: The combined use of sFlt-1/PlGF ratio with PlGF or sFlt-1, improved the predictive and diagnostic performance of each separate marker.